FRI0006 Association Between the Increased Frequencies of Peripheral Blood Double-Negative (IGD-CD27-) B-Cell Subset and Disease Activity in Systemic Lupus Erythematosus. (9th June 2015) - Suponitskaya, E.; Aleksankin, A.; Mesnyankina, A.; Panafidina, T.; Aleksandrova, E.; Solovyev, S.; Nasonov, E.
Abstract : Background: Alterations of B-cell subset distribution have been described in the peripheral blood of systemic lupus erythematosus (SLE) patients (pts), but data are still controversial and association between B-cell subsets and SLE activity remains unclear. Objectives: To examine B-cell subsets in peripheral blood of healthy donors and active SLE pts by flow cytometry before Rituximab (RTX) treatment, and to analyze the association between B-cell subsets and SLE activity. Methods: 23 active SLE pts (21F/2M); median age 36 years (range) (30-40); disease duration 6.7 years (2-8); SLEDAI-2K score 13.5 (8-19), SLEDAI-2K≥8 in 18 pts, SLEDAI-2K<8 in 5 pts; global BILAG index (calculated by i-BLIPS softwear) 20.5 (14.5-24) were assessed before RTX treatment for B-cell subsets and laboratory data: ESR, CRP, C3, C4, ANA, anti-dsDNA Ab. All pts were treated with prednisolone 17.5 (10-25) mg/day, mycophenolate mofetil (7pts), azathioprine (5pts), antimalarials (19pts), methotrexate (1pts). CD19+B cells, memory B cells (CD19+CD27-), non-switched memory B cells (CD19+IgD+CD27+), switched memory B cells (CD19+IgD-CD27+), naïve (CD19+IgD+CD27-), double-negative (CD19+IgD-CD27-), transitional (CD19+IgD+CD10+CD38++CD27-) B cells, and plasmablasts (CD19+CD38+++IgD-CD27+CD20-) were analyzed using multicolor flow cytometry. Results: The median percentages (range) of memory B cells (CD19+CD27+), non-switched memory B cells (CD19+IgD+CD27+), naïve (CD19+IgD+CD27-), and transitional (CD19+IgD+CD10+CD38++CD27-) B cells were lower in SLE pts compared to healthy donors (N=27): 1.3% (1.0-2.2) vs 2.2% (1.6-3.3), 2.1% (1.6-5.9) vs 10.0% (6.4-12.7), 58.2% (40.2-66.9) vs 65.8% (55.1-73.4), and 0.1% (0-0.1) vs 0.1% (0.1-0.3), respectively, p<0.05 for all cases. The percentages of double-negative B cells (CD19+IgD-CD27-) in SLE pts were higher than in healthy donors: 29.6% (20.9-41.3) and 9.8% (8.4-12), respectively, p<0.0001. In total SLE cohort, we found a negative association of the frequencies (r=-0.59) and absolute numbers (r=-0.59) of memory B cells (CD19+CD27+) with anti-dsDNA Ab levels, p<0.05 for both cases. The frequencies of double-negative B cells (CD19+IgD-CD27-) correlated positively with SLEDAI-2K (r=0.55), BILAG (r=0.55), ESR (r=0.60), and daily prednisolon dosage (r=0.50), p<0.05 for all cases. In active SLE pts (N=18, SLEDAI-2K≥8) this correlation was even higher: for SLEDAI-2K: r=0.67, BILAG: r=0.75, ESR: r=0.79. A strong negative association of the frequencies of double-negative B cells (CD19+IgD-CD27-) with C3 and C4 levels was observed in 17 pts with high anti-dsDNA Ab titers (>50 IU/ml): r=-0.80 and r=-0.59, respectively, p<0.05 for both cases. Conclusions: Immunophenotyping showed the decreased frequencies of memory, non-switched, naïve, transitional B-cell and increased frequencies of double-negative B cells in our active SLE cohort. Positive correlation between the level of double-negative B cells and disease activity indexes (SLEDAI-2K, BILAG), ESR, as well as a strong negative association with C3 and C4 could suggest that IgD-CD27- B cells play a prominent role in SLE pathogenesis. Acknowledgements: The authors thank Prof. H.-P. Tony, A. Koss-Kinzinger, and Z. Mahmood (University of Wuerzburg, Germany) for the assistance in the analysis of preliminary results. Disclosure of Interest: None declared